Evolution of European sea bass (Dicentrarchus labrax) freshness during storage - Gerolamo Xiccato (Italian Journal of Animal Science, 2010)
The study aimed to assess freshness evolution in 90 European sea bass (Dicentrarchus labrax) analyzed 2h after catch (day 0) and after 1, 2, 4, 6, and 8 days of storage at 2°C. Sea bass weighted 308±37g with average carcass yield of 89.8% and fillet yield of 48.8% slaughter weight. During storage skin colour indexes linearly changed (L<0.01) showing higher L* and lower a* and b* values. The eye liquor pH increased with storage, with both significant linear and quadratic components of variance. Fillet hardness increased from day 0 to day 4 and then decreased on day 8 (quadratic component of variance <0.01). Sensory freshness assessed by Quality Index Method showed a quadratic evolution and high correlation (R2=0.95) with days of storage.